Sistem Work From Home, kemampuan manajerial, dan komitmen organisasi perannya pada kinerja - Sindy Andani Iryanti; Endi Sarwoko; Pieter Sahertian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2021)
This study aims to determine the effect of managerial ability, commitment, and work from home system on performance. This research uses quantitative research on Bhakti Pertiwi Junior High School teachers with a total sample of 63 people. Data were collected using a questionnaire designed using a 5-point Likert Scale. Managerial ability is the ability of the principal in carrying out management functions. Commitment is measured by affective, continual, and normative commitment. The work from home system is a time flexibility that will affect the discipline, responsibility and creativity of teachers. Data analysis technique using Multiple Linear Regression. The results of the study reveal that teacher performance is influenced by the ability of the principal's manager, also influenced by the level of commitment to the profession. In addition, the implementation of work from home during the Covid-19 pandemic did not cause teacher performance to decrease, it was actually able to improve teacher performance.